RELAÇÕES ENTRE O TRATAMENTO DE SEMENTES DE SOJA, OS PARÂMETROS FISIOLÓGICO E SANITÁRIO E A CONSERVAÇÃO DAS SEMENTES - Bail, José Luciano (2013)
Sowing soybean seed in the field is a key component to obtain economically yields. The chemical treatment is essential to promote the vigorous development of seedlings and ensure ideal stand establishment of plants. However it is essential to know the relationship between the products used and seed quality parameters. This study aimed to assess the health and physiological attributes of soybean seeds treated with combinations of products and stored for different periods of time in a natural environment. The soybean seeds, cultivars BRS 284 and Don Mario 7.0i, were harvested on 2011 in Ponta Grossa, PR. The treatments consisted of the use of the fungicide thiram + carbendazin (F), (200 mL of the commercial product per 100 kg of seed) the same fungicide in combination with the insecticide Fipronil (FI), (200 ml of the commercial product per 100 kg of seed), this fungicide in combination with micronutrient CoMo (FM), (300 ml of the commercial product per 100 kg of seed) and the same fungicide and insecticide combined with the micronutrient, using that doses indicated (FIM) and control treatment, seed without these products. The seeds were analyzed immediately after the onset of treatments and at 45, 90 and 135 days of storage. Besides the determination of moisture content, seed quality was evaluated by germination, emergence and seedling length and seed pathology. The experimental design was a completely randomized design with four replicates for each test and comparison of means by Tukey test (5%). There is no negative influence of the soybean seed treatment on seed conservation. The application of fungicide, insecticide alone or associated with micronutrient improve the sanitary quality of seeds in both cultivars, immediately after treatment and during seed storage time.